Pengembangan Model Rantai Pasok Pisang Mas di Lumajang dan Malang - Gunawan, Gerry Anggian; Widyadana, I Gede Agus; Palit, Herry Christian (Jurnal Titra, 2014)
Pisang Mas (Musa acuminata colla) is one of important commodities in East Java. Previous study showed that there are two different supply chain models at Lumajang and at Malang. In these paper, we combine different supply chain models and considers the effect of price on customer demand. This model is simulated using Vensim PLE software. The result shows that demand is affected by price change. This model is sensitive to price with percentage of 12,4% in retail and 13,04% in traditional market.